Effect of the number of dose adjustment factors on bleeding risk in patients receiving 30 mg/day edoxaban. (11th October 2019) - Takase, Tomoki; Ikesue, Hiroaki; Nakagawa, Haruna; Kinoshita, Megumi; Muroi, Nobuyuki; Kitai, Takeshi; Furukawa, Yutaka; Hashida, Tohru
Abstract: What is known and objective: Edoxaban has three dose adjustment factors (creatinine clearance, 15‐50 mL/min; body weight, 60 kg or less; and concomitant medication with potent P‐glycoprotein inhibitors) to prevent bleeding that results from elevated blood concentrations of the drug. A dose reduction (from 60 to 30 mg/day of edoxaban) is recommended for patients with even one of those. However, it is not clear whether 30 mg/day of edoxaban is adequate for patients with multiple dose adjustment factors. We thus investigated the association between the number of the dose adjustment factors and bleeding risk in patients receiving edoxaban. Methods: We retrospectively analysed 198 patients who received 30 mg/day of edoxaban between April 2015 and March 2017 with follow‐up for 1 year. Results: The incidences of major bleeding were 1.4%, 7.3% and 20.0% in patients with 0‐1, 2 and 3 dose adjustment factors, respectively. The Cox proportional hazards regression model revealed that the risk of major bleeding was higher in patients with 2 (hazard ratio [HR]: 5.80, 95% confidence interval [CI]: 0.96‐44.05, P  = .055) or 3 (HR: 17.70, 95% CI: 2.12‐147.70, P  = .012) dose adjustment factors than in those with 0‐1 dose adjustment factor. What is new and conclusion: This is the first study to evaluate the risk of bleeding in patients administered 30 mg/day of edoxaban based on the number of dose adjustment factors in clinical practice. For patients receiving edoxaban, as the number of the dose adjustment factors increases, the risk of major bleeding is elevated. In patients with multiple dose adjustment factors, not only one level of dose reduction, but further dose reductions may be considered. Further studies with a larger sample size are needed to confirm these findings. Abstract : Kaplan‐Meier curves of major bleeding (A) and clinically relevant non‐major bleeding (B) based on the number of dose adjustment factors (creatinine clearance 15‐50 mL/min, body weight ≤ 60 kg, or concomitant treatment with potent P‐glycoprotein inhibitors). Thick line: patients with 3 dose adjustment factors. Thin line: patients with 2 dose adjustment factors. Grey line: patients with 0‐1 dose adjustment factor.